Analysis of some issues in current innovation support models and some suggestions under Vietnam’s conditions - Nguyen Xuan Hoa; Tran Vu Tuan Phan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2022)
The Vietnamese government and Communist party of Viet Nam have affirmed that innovation is the driving force for the country’s development. However, innovation activities are still limited due to the lack of supportive models. Therefore, having innovation support models is urgent and necessary. Currently, innovation support models operate individually, without a clear system, leading to unclear results and ineffective promotion of innovation activities. Identifying issues in current innovation support models in Vietnam is significant in suggesting development policies to support innovation activities in the country. Code: 23021001